2012
DOI: 10.1590/s0100-67622012000600017
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characteristics and Kraft pulping of tension wood from Eucalyptus globulus labill

Abstract: -Tension (TW) and opposite wood (OW) of Eucalyptus globulus trees were analyzed for its chemical characteristics and Kraft pulp production. Lignin content was 16% lower and contained 32% more syringyl units in TW than in OW. The increase in syringyl units favoured the formation of β-O-4 bonds that was also higher in TW than in OW (84% vs. 64%, respectively). The effect of these wood features was evaluated in the production of Kraft pulps from both types of wood. At kappa number 16, Kraft pulps obtained from TW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
4
5
0
Order By: Relevance
“…Target ISO brightness was 90% (mean 89.3% ±1.6 for all samples). The intrinsic viscosity of the pulps was low compared to the 942 to 1274 mL.g -1 reported by Santos et al (2008), but similar to the 821 mL g -1 in Aguayo et al (2012) for E. globulus pulps. The mean amount of ClO2 consumed (as active chlorine) was 4.8%, with variations due to the different initial kappa number of the unbleached pulps (Table 1).…”
Section: Raw-materials Characterizationsupporting
confidence: 72%
“…Target ISO brightness was 90% (mean 89.3% ±1.6 for all samples). The intrinsic viscosity of the pulps was low compared to the 942 to 1274 mL.g -1 reported by Santos et al (2008), but similar to the 821 mL g -1 in Aguayo et al (2012) for E. globulus pulps. The mean amount of ClO2 consumed (as active chlorine) was 4.8%, with variations due to the different initial kappa number of the unbleached pulps (Table 1).…”
Section: Raw-materials Characterizationsupporting
confidence: 72%
“…The small difference in residual lignin between heartwood and sapwood pulps (11.2 vs. 9.5 for corrected Kappa number) may be explained by some cell wall waterproofing from the heartwood extractives decreasing liquor penetration and increasing chemical consumption (Hillis 1987;Gutiérrez et al 2001;Rowell et al 2005). The intrinsic viscosity of the pulps was slightly lower compared to the 942-1274 cm 3 /g reported by Santos et al (2008) but similar to the 821 cm 3 /g reported by Aguayo et al (2012) for E. globulus pulps. The kraft pulps produced from the overaged samples develop bleaching in a similar way to the industrial wood chips.…”
Section: Discussionsupporting
confidence: 67%
“…increasing wood flexibility and tolerance to mechanical perturbations). The relative reduction of xylan in tension wood and the increase in α‐cellulose are consistent with the generally accepted model of physicochemical changes in tension wood, but do not agree with previous tension wood physicochemical characterizations of E. globulus that showed an increase in xylan and no change in cellulose (Aguayo et al ., , ), although a reduction in lignin is consistently found.…”
Section: Discussionmentioning
confidence: 99%